A new bio-inspired stimulator to suppress hyper-synchronized neural firing in a cortical network. (7th December 2016) - Amiri, Masoud; Amiri, Mahmood; Nazari, Soheila; Faez, Karim
Abstract: Hyper-synchronous neural oscillations are the character of several neurological diseases such as epilepsy. On the other hand, glial cells and particularly astrocytes can influence neural synchronization. Therefore, based on the recent researches, a new bio-inspired stimulator is proposed which basically is a dynamical model of the astrocyte biophysical model. The performance of the new stimulator is investigated on a large-scale, cortical network. Both excitatory and inhibitory synapses are also considered in the simulated spiking neural network. The simulation results show that the new stimulator has a good performance and is able to reduce recurrent abnormal excitability which in turn avoids the hyper-synchronous neural firing in the spiking neural network. In this way, the proposed stimulator has a demand controlled characteristic and is a good candidate for deep brain stimulation (DBS) technique to successfully suppress the neural hyper-synchronization. Highlights: A new bio-inspired stimulator based on the mathematical model of the astrocyte is proposed. A large-scale spiking neural network is used to evaluate the performance of the proposed stimulator.. The bio-inspired stimulator has a demand controlled characteristic and is a good candidate for DBS technique.